1984
DOI: 10.1172/jci111644
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of apolipoprotein B in large triglyceride-rich very low density lipoproteins of normal and hypertriglyceridemic subjects.

Abstract: Abstract. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
104
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(115 citation statements)
references
References 26 publications
11
104
0
Order By: Relevance
“…Original studies showed that a precursor-product relationship existed between VLDL and LDL in normolipidemic individuals (26-28) (i.e., all VLDL was converted to LDL, and all LDL was derived from VLDL). In more recent studies (30)(31)(32)(33), however, it has been shown that a significant proportion of VLDL apo B can be cleared from the plasma by receptor-mediated uptake (presumably in the liver) (arrow 2, Fig. 8) and is therefore not converted to LDL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Original studies showed that a precursor-product relationship existed between VLDL and LDL in normolipidemic individuals (26-28) (i.e., all VLDL was converted to LDL, and all LDL was derived from VLDL). In more recent studies (30)(31)(32)(33), however, it has been shown that a significant proportion of VLDL apo B can be cleared from the plasma by receptor-mediated uptake (presumably in the liver) (arrow 2, Fig. 8) and is therefore not converted to LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects have therefore been studied during periods of both fasting and feeding. In previous VLDL apo B kinetic studies (26)(27)(28)(29)(30), fat-and calorie-restricted diets have been given to minimize the secretion of chylomicrons and VLDL from the intestine. This rather artificial situation, however, represents neither a fasted nor fed state.…”
Section: Discussionmentioning
confidence: 99%
“…23 Once in the circulation, the larger VLDL species are lipolyzed by lipoprotein lipase, and most of the remnant particles formed in this process are removed from the circulation before reaching a particle size or density corresponding to LDL. 26 Small VLDL particles, on the other hand, seem to be direct precursors of LDL, as the secretion rate of small VLDL is tightly linked to the LDL cholesterol concentration in plasma. 27 It could thus be speculated that enhanced function of MTP, as would occur with the rare MTP Ϫ493 T promoter variant we have described, acts by shifting the balance between secretion of large and small VLDLs.…”
Section: Discussionmentioning
confidence: 99%
“…34 -36 In both normal and hypertriglyceridemic subjects, the VLDL 3 density subclass contains at least two metabolically distinct particle populations. 35 One of these is derived from large triglyceride-rich VLDL, S f >60, and its turnover within the interval S f 12-100 is slow, with little reaching LDL (S f 0-12). The other particle within the VLDL 3 subclass is rapidly turned over into LDL and represents a major precursor.…”
Section: Discussionmentioning
confidence: 99%
“…The other particle within the VLDL 3 subclass is rapidly turned over into LDL and represents a major precursor. 35 VLDL 3 is also the subclass in which LDL receptor binding can be mediated by either apoE or apoB in hypertriglyceridemic subjects, 32 -37 further indicating metabolic heterogeneity and at least two subpopulations within this subclass. Although the average K A of binding of VLDL 3 to the LDL receptor did not change after treatment, as measured in vitro (Table 5), there may be changes in the metabolism of this subclass in vivo (i.e., increased transport into this subclass from VLDL!…”
Section: Discussionmentioning
confidence: 99%